Practical Emergency Ultrasound Flashcards with Augmented Reality in Teaching Point-of-Care Ultrasound in ER - Ienghong, Kamonwon; Kotruchin, Praew; Tangpaisarn, Thanat; Apiratwarakul, Korakot (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The use of point-of-care ultrasound (POCUS) has recently proposed the integration of ultrasound into undergraduate medical education. However, the evidence of learning tool for this integration has not been well studied. AIM: The aim of this study was to compare the levels of knowledge improvement of the 6th year medical students before and after receiving the POCUS training in two ways: By employing the traditional methods and by utilizing the new learning tool. METHODS: The practical ultrasound flashcards were developed by a Thai physician. In the study, the 6th year medical students were enrolled and randomized to become members of either the flashcard group or the control group. Participants in both groups attended a 4-week ultrasound training course. Before and after the training course, all students were evaluated using the multiple-choice questions. In addition, the subjects’ attitudes and perceptions about the flashcards were evaluated using a questionnaire. RESULTS: A total of 46 students participated in this study and were randomly assigned to either the flashcard group (n = 23) or the control group (n = 23). It was discovered that the students in the flashcard group had performed better on the POCUS knowledge post-test than those in the control group had. Most students had been satisfied with the flashcards (mean 5 Likert scores = 4.48). However, the students had rated their confidence score to perform POCUS at 3.96 out of 5.0. CONCLUSIONS: Medical students who used the ultrasound flashcards to learn POCUS had resulted in better knowledge scores rather than the others who attended the standard ultrasound training course only. However, it was not possible to evaluate the practical skills and the clinical decision-making processes in this study.